Interpersonal Competence of Adolescents Living in the Darul Ma'arif Orphanage, Olo Nanggalo Village, Padang City - Suhatril, Shalsa Fadila (Lembaga Riset Mutiara Akbar, 2022)
This research is motivated by the phenomenon that teenagers live in orphanages who are not able to adjust themselves in the orphanage environment and the environment outside the orphanage. The purpose of this study is how the interpersonal competence of adolescents is seen from the aspects: (1) the ability to take initiative (2) the ability to be open (3) the ability to be assertive (4) the ability to provide emotional support (5) the ability to overcome conflict. This type of research is descriptive quantitative. The population of this study was 24 teenagers at the Darul Ma'arif Orphanage in Olo Nanggalo Village, Padang City. The sample in the study was 24 adolescents taken using a non-probe sampling technique or also known as a saturated sample. The instrument used in this study is a questionnaire and for data analysis using descriptive statistics with percentage techniques. The results of the research on the Interpersonal Competence of Adolescents who Live in the Darul Ma'arif Orphanage in Olo Nanggalo Village, Padang City, are seen from: (1) The ability to take initiative is in the good category, (2) The ability to be open is in the good category, (3) The ability to be assertive is in the good category, (4) the ability to provide emotional support is in the very good category, (5) the ability to resolve conflict is in the good category. Based on the findings of this study, the researcher recommends that adolescents who live in orphanages should take part in positive activities both held in the orphanage and in schools so that adolescents can hone, become bolder in developing the potential that exists in themselves and so that adolescents can interact with each other. friends to avoid feeling lonely and further improve interpersonal competence.